Polyethyleneimine-modified magnetite prepared without a base to remove Congo red in water. Issue 1 (2022) - Liu, Yu; Gan, Ying; Zhao, Cong; Xie, Maoqiong; Gu, Dongxu; Shuai, Shirong; Zhu, Hongyu; Hao, Jianyuan
Abstract : Polyethyleneimine-modified magnetite (Fe3 O4 @PEI) with excellent stability within a wide pH range in aqueous solution was synthesized by only one-step coprecipitation in the absence of other bases. PEI was used as the precipitant and the stabilizer. The preparation condition was optimized, and the role of PEI was also clarified. The crystallization process of magnetite only in the presence of PEI was different from others with ammonia solution added as a base. The adsorption behavior of Fe3 O4 @PEI on anionic dyes, including methyl blue, orange I and Congo red (CR), was studied. Highly efficient adsorption of CR was observed within a wide pH range (2–10). Saturated adsorption could be achieved within 10 min. The isotherm and kinetics revealed the multimolecular layer chemisorption of CR. After the fourth cycle, the adsorption efficiency of CR was still above 98%. This research provided a very simple method for removing CR in aqueous solution with high efficiency.